1999
DOI: 10.1021/jp991683b
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Thiophene, Pyridine, and Cyclohexylamine on Ni/MoSxand Ni/S/Mo(110) Surfaces:  Role of Nickel in Hydrodesulfurization and Hydrodenitrogenation Processes

Abstract: Synchrotron-based high-resolution photoemission has been used to study the interaction of thiophene, pyridine, and cyclohexylamine (CHA) with pure and Ni-promoted MoS x films and S/Mo(110) surfaces. The MoS x films exhibit Mo 3d and valence spectra that are very similar to those of MoS 2 . On the MoS x systems, the behavior of thiophene closely resembles that seen on MoS 2 (0002). The molecules are weakly chemisorbed, and most of them desorb at temperatures around 200 K. A small fraction of the adsorbed thioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
(194 reference statements)
1
6
0
Order By: Relevance
“…This was also confirmed for W/Al 2 O 3 and NiW/ Al 2 O 3 catalysts prepared from either the oxy-salts or thio-salts (127,239). For the latter catalysts (ATT/Al 2 O 3 ), neither activation energy nor heat of adsorption were changed by the addition of fluoride (125,237). The similar activation energy found for both pathways in Fig.…”
Section: Hydrodenitrogenation Of Petroleumsupporting
confidence: 74%
See 2 more Smart Citations
“…This was also confirmed for W/Al 2 O 3 and NiW/ Al 2 O 3 catalysts prepared from either the oxy-salts or thio-salts (127,239). For the latter catalysts (ATT/Al 2 O 3 ), neither activation energy nor heat of adsorption were changed by the addition of fluoride (125,237). The similar activation energy found for both pathways in Fig.…”
Section: Hydrodenitrogenation Of Petroleumsupporting
confidence: 74%
“…Topsøe et al (6,236) showed that Ni promoter facilitates formation of a catalytically active Ni -Mo(W) -S phase. The enhancement in HDN activity of the NiMoS 2 system compared with that for unpromoted MoS 2 observed by Rodriguez et al (237), was attributed to the ability of Ni to supply active hydrogen. As a consequence, the reducibility of the sulfide phase is improved.…”
Section: Vi12 Involvement Of Ni and Co In Hdnmentioning
confidence: 81%
See 1 more Smart Citation
“…The sample was flashed to temperatures in the range of 1800−2500 K using an e-beam heater. Standard procedures were followed to remove carbon (heating in O 2 at 700−1000 K, and subsequent ion sputtering or fast heating to 2000 K) and sulfur (ion sputtering and/or fast heating to 2500 K) from the Mo crystal. Surfaces of carbide-modified molybdenum were prepared by exposing the Mo(110) sample to large doses of ethylene at 600 K, followed by annealing to 1200 K. , After 4−6 cycles of C 2 H 4 dosing/annealing, a good (4 × 4) pattern was seen with low-energy electron diffraction (LEED) for the carbide overlayers.…”
Section: Methodsmentioning
confidence: 99%
“…The films exhibit Mo 3d and S 2p XpS spectra that are very similar to those of MoS2. They show no reactivity toward CO, 02 or H2 at 1(90-400 K. But they can be activated after the creation of S vacancies by reaction with atomic H [62], providing convenient surfaces for examining the chemistry of desulfi.uizationreactions on molybdenum sulfide [63].…”
Section: Admetal Promoted Sulfidation Of Pt(lll) and Mo(11o)mentioning
confidence: 99%